THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON STATE CIVIL APPARATUS (ASN) PERFORMANCES IN THE REGIONAL CIVIL SERVICE AGENCY IN GORONTALO PROVINCE - Djibran, Nadesyia; Ilato, Rosman; Aneta, Yanti (Public Policy Journal, 2021)
This research aims to analyze the effect of work motivation and work discipline on state civil apparatus (ASN) performances in the Regional Civil Service Agency (BKD) in Gorontalo Province, either partial or simultaneous. The research method used was quantitative. The data analysis used was double regression. Research findings demonstrate that 1) The partial test attested to a significant effect of work motivation on employee performances in BKD in Gorontalo Province by 38.07%, 2) The partial test indicated a significant effect of work discipline on employee performances in BKD in Gorontalo Province by 48.72%, and 3) The simultaneous test justified that 68.2% of the employee performance variability in BKD in Gorontalo Province was affected by employee work motivation and work discipline, whereas the rest, 31.8%, was affected by other variables.